High serum neurofilament levels among Chinese patients with aquaporin-4-IgG-seropositive neuromyelitis optica spectrum disorders. (January 2021) - Liu, Chunxin; Zhao, Lin; Fan, Ping; Ko, Ho; Au, Cheryl; Ng, Angel; Au, Lisa; Wong, Adrian; Kermode, Allan G.; Mok, Vincent; Yan, Yaping; Qiu, Wei; et al.
Highlights: Subjects with MS and NMOSD have higher sNfL levels as compared to HCs. Higher sNfL levels during an MS or NMOSD attack. Lower levels among subjects treated with immunosuppressants for NMOSD subjects. sNfL levels were not significantly different between CSF OCB-positive and negative patients. Abstract: Background: Serum neurofilament light chain (sNfL) is a promising biomarker for neuromyelitis optica spectrum disorders (NMOSD) and multiple sclerosis (MS), but there is limited validation data in specific ethnic and disease groups. Objective: To investigate the levels of sNfL in a cohort of Chinese patients with NMOSD and compare sNfL levels in patients with different disease courses and treatments. Methods: We analysed sNfL levels in 153 Chinese patients with NMOSD (n = 51) and MS (n = 102) using single-molecule array (Simoa) technology. The sNfL levels were compared with those of 71 healthy controls from two centres in southern China. For each disease, we assessed correlations between sNfL and disease phases and treatments. Results: Higher levels of sNfL were found in the patients with NMOSD [17.97 (10.55–27.94) pg/mL] and MS [15.83 (8.92–25.67) pg/mL] compared to healthy controls [10.09 (7.19–13.29) pg/mL, p  < 0.001]. No significant differences were found between the AQP4-IgG-positive NMOSD group and OCB-positive MS group. Conclusions: sNfL measured by Simoa technology is a potential candidate blood biomarker for the diagnosis and disease monitoring of NMOSD in Chinese patients, warranting further prospective and multicentre studies.